ATTITUDES OF NURSES WORKING IN COVID-19 UNITS TOWARDS NURSING PROFESSION: A CROSS-SECTIONAL STUDY - Saatçi, Gamze; Ünsal, Aylla (Göbeklitepe Medical Science Journal, 2024)
The COVID-19 pandemic has not only physical but also psychological effects on nurses due to the unpredictability of the contagiousness and effects of the disease. These effects affect the professional attitudes of nurses.The aim of the study was to examine the attitudes of nurses working in COVID-19 units towards their profession. In this cross-sectional descriptive study, a correlational design was used to examine the professional attitudes of nurses working in COVID-19 emergency, intensive care and ward units of different hospitals in Turkey. Data were collected through an online questionnaire administered to 351 nurses between March and May 2022 and analysed using SPSS for Windows 25 package software. Statistical methods such as t-test in independent groups, analysis of variance in multiple groups and multiple regression analysis in correlational inferences were used in the analyses. The mean total score of the "Attitude Towards Nursing Profession Scale" of the nurses participating in the study was 161.34 ± 14.49. There was no statistical difference between the professional attitudes of the nurses and the unit they worked in (p=,579). In this study, nurses' attitudes towards their profession were found to be high. During the pandemic period, the professional attitudes of nurses do not change according to the